Inclusion of the latent personality variable in multinomial logit models using the 16pf psychometric test (2012)
Travel demand models typically use modal attributes and socioeconomic characteristics as explanatory variables.It has been established that attitudes and perceptions as well as individual psychological variables influencea user's behavior. In this study, the latent personality variable was included in the estimation of a hybrid discrete choice model to incorporate the effects of subjective factors. The latent personality variable was assessed with the 16PF psychometric test,which has been widely use by researchersworldwide. The paper analyzes the results of applying this model to a sample of employees and university professors and proposes a way in which the psychometric tests can be used in hybrid discrete choice models. Our results show that hybrid models that include latent psychological variables are superior to traditional models that ignore the effects of user'sbehavior.